Epigenetics of Myotonic Dystrophies: A Minireview - Virginia Veronica Visconti (MDPI AG, 2021)
Myotonic dystrophy type 1 and 2 (DM1 and DM2) are two multisystemic autosomal dominant disorders with clinical and genetic similarities. The prevailing paradigm for DMs is that they are mediated by an in trans toxic RNA mechanism, triggered by untranslated CTG and CCTG repeat expansions in the DMPK and CNBP genes for DM1 and DM2, respectively. Nevertheless, increasing evidences suggest that epigenetics can also play a role in the pathogenesis of both diseases. In this review, we discuss the available information on epigenetic mechanisms that could contribute to the DMs outcome and progression. Changes in DNA cytosine methylation, chromatin remodeling and expression of regulatory noncoding RNAs are described, with the intent of depicting an epigenetic signature of DMs. Epigenetic biomarkers have a strong potential for clinical application since they could be used as targets for therapeutic interventions avoiding changes in DNA sequences. Moreover, understanding their clinical significance may serve as a diagnostic indicator in genetic counselling in order to improve genotype–phenotype correlations in DM patients.